PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT KISEL (ANAK PERUSAHAAN PT TELKOMSEL) MEDAN - Muhammad Yamin Siregar; Intan Wahyu Ningsih (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The objective of this research is to determine the impact of service quality dimension viewed from tangible,  reliability,  responsiveness,  assurance,  and  empathy  dimension  towards  customer satisfaction at PT. Kisel (Official Branch of PT. Telkomsel) Medan.In this research the population’s 103  respondent  with  sample’s  used  is  82  respondent.  The  sample  selection  method  used  is purposive sampling, based on Telkomsel customer that visit PT Kisel to complaint their problem more  than  1  time.  Data  analyzing  method  that  is  used  is  multiple  linear  regression  using  SPSS version 19.0 program.The result of this research is  tangible, reliability, responsiveness, assurance, empathy simultaneously have positive and significant influencetoward customer satisfaction. Based on  test  only  reliability  variable  and  assurance  have  significant  influence  towards  customer satisfaction. based on coefficient determination test (  R2) 86,3% of customer satisfaction can be explained by tangible, reliability, responsiveness, assurance, and empathy, while the rest 13,7% is explained by other variables not observed in this research.Keywords :Tangible, Reliability, Responsiveness, Empathy, Customer satisfaction